Geografia eleitoral e identidade: um estudo de caso da zona norte de Goiânia - Nogueira, Braian de Alencar (2020)
Firstly, it is discussed how the electoral systems in force in Brazil works. Next, the main authors and methods of Electoral Geography are approached, so that we can finally discuss the 2016 elections in Goiânia and later analyse the spatial distribution of votes. The votes of the six most well-voted candidates in the North Zone of Goiânia were analysed, being them: Vinicius Cirqueira (PROS), Jorge Kajurú (PRP), Sergeant Novandir (PTN), João Araújo (PT), Jorge (PR) and Mauricio Beraldo (PSDB). The second part of the dissertation focuses on identifying the influence of Vinicius Cirqueira’s territorial identity on the behaviour of local voters (influence of territorial identity on elections). The methodology used is based on a bibliographic survey on identity and territory, candidate’s history, mapping of votes, and the electoral connection based on the count of words used in their social network linked to their electoral base and the quantitative assessment of its legislative production aimed at the electoral base. The results of the observation of the 2016 municipal election showed the candidates who obtained the support of the mayor elected in the same election, Iris Resende, and the incumbent Governor, Marconi Perillo, were more successful in the elections for the City Council.With the mapping of the spatial distribution of the votes of the six best-voted candidates in the Northern Zone of Goiânia, the neighbourhoods forming their electoral territories (or electoral base) of each candidate were identified, allowing to identify that most of the electoral territories are formed by localities where the candidate has a connection as a resident, professional or with social actions. By evaluating the spatial patterns of voting through the Ames typology, the result was a majority of the candidates with concentrated-shared profile, having their votes concentrated in a few voting locations, but without being able to dominate them. For the study of Vinicius Cirqueira’s territorial identity, the conclusion was that the candidate is linked to his electoral base because he lives in the area and obtains his votes from the territorial identification in common with his electorate.